Penerapan Storyboard Dalam Pengembangan Media Interaktif Pembelajaran Drama untuk Mengatasi Bullying di SMP - halimah, Halimahtusyadiyah; Taqdiraa, Taqdiraa; Khairiyah, Ayu; Putri, Nina Queena Hadi; Suhatmady, Bibit (Universitas Negeri Padang, 2025)
Bullying is one of the serious social problems in the school environment, especially at the Junior High School (SMP) level. Bullying behavior not only affects students' academic achievement but also threatens mental health and character formation. Unfortunately, learning in schools often does not explicitly touch on this issue. This study aims to design and implement interactive learning media based on storyboards in drama learning as an educational effort to increase students' awareness of bullying. The method used is research and development (R&D) with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The subjects of the study were grade VIII junior high school students who were involved in making storyboards with the theme of bullying and implementing drama simulations. The results of the study showed that the use of storyboards as interactive media was able to increase participation, understanding of the storyline, and build empathy and courage in students in dealing with bullying issues. Drama simulations are an effective means for students to express ideas reflectively and contextually. This study recommends the integration of interactive media and acting in the curriculum as a contextual learning strategy that not only educates but also shapes students' character as a whole.Keyword: bullying, storyboard, drama, interactive media, contextual learning